Capital And Operating Cost Estimating System Manual For Mining And Beneficiation Of Metallic And Nonmetallic Minerals Except Fossil Fuels In The United States And Canada ? 1. Introduction ? 1.1 Need For The Handbook (The National Institute for Occupational Safety and Health (NIOSH), 2012)
The United States Bureau of Mines is establishing a computerized mineral inventory system to help the Federal Government appraise its mineral position and prepare programs insuring against critical shortages of materials. This system, called the Minerals Availability System (MAS), is a component of the Bureau's minerals intelligence function designed to conduct and maintain an inventory of minerals important to the Nation. The MAS defines the physical and commercial availability of the mineral resources. Known resources are evaluated and classified by deposit for entry into a computer storage and retrieval system. An integral concern of these evaluations is the cost of mining and beneficiating the ore contained in specific deposits. To meet this concern, a cost handbook was developed as an aid to preparing feasibility-type estimates for capital and operating costs of mining and primary beneficiation of various types of mineral occurrences. Cost data, obtained from U.S. and Canadian companies, were used as the basis of this handbook. The handbook presents cost curves and equations for each component of the mining and beneficiation process. Factors for each cost component are also given, thereby allowing the updating of cost for time, geographic location, labor rates, and mining and milling conditions. Included in the latter conditions are items such as the length of haul, need for rock bolts, and a rock work index for ores and rocks of various hardnesses. 1.2. USE OF THE HANDBOOK Using the handbook a feasibility-type estimate falling within 25% of expected actual cost is obtainable by summarizing cost components. This handbook should not be used to determine the cost of any single component of a mining or beneficiation system, as any single component may not fall within the 257 limit. It must be understood that anyone who uses the handbook must have a comprehensive knowledge of mining and processing technology and cost estimating procedures. The handbook was intended to be used internally by the Minerals Availability System. Because